Avaliação clínica de restaurações de resina composta em dentes anteriores e posteriores - Baldissera, Rudimar Antônio (2012)
Composite restorations are daily performed in dental offices; however, few studies have reported the longevity of these restorations for long periods of observation. This study was conducted to evaluate the clinical performance of resin composite restorations placed in anterior and posterior teeth in the period between the years 1991 and 2001. From the files of a private dental clinic, 83 patients who received 375 restorations in posterior teeth and 61 patients with 237 restorations in anterior teeth with the composites Charisma (Heraeus Kulzer, Hanau, Germany), Herculite XR (Kerr, Orange, CA, USA) or Z100 (3M ESPE, St. Paul, MN, USA) participated in the study, being examined by two calibrated researchers. The restorations were evaluated according to the FDI criteria (World Dental Federation, HICKEL et al., 2007). After the fieldwork, data were double tabulated and subjected to statistical analysis using Stata version 11.0. Descriptive statistics were used to report the frequency of distribution of the restorations for the variables evaluated and for the causes of failures. The survival analyzes were performed using the Kaplan-Meier method, to obtain the survival curves for the variables of interest, followed by the Log-Rank test for comparison between groups (α=0.05). The analysis of factors associated with failure over time was performed using a model of multivariate analysis by Cox regression with shared fragility. Of the total of 612 restorations, 69 were considered unsatisfactory. The annual failure rate observed at the final of the period was 0.76 to anterior teeth and 1.16 to posterior teeth. The aesthetic factor was the major cause in the anterior teeth, while in posterior were the fractures. Regarding the material, the composite Herculite was significantly better than Z100 and this better than Charisma. Restorations with the largest number of surfaces involved had the worst performance. The result of this study showed a satisfactory clinical performance. In relation of the material, the composite Herculite was significantly better than the Z100 and this better than Charisma. The restorations with the highest number of surfaces involved had the worst performance